2018
DOI: 10.1002/anie.201709417
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Atom Hybridization Matters: Ultrafast Humidity Response of Graphdiyne Oxides

Abstract: Graphdiyne oxide (GDO), the oxidized form of graphdiyne (GDY), exhibits an ultrafast humidity response with an unprecedented response speed (ca. 7 ms), which is three times faster than that of graphene oxide (GO) with the same thickness and O/C ratio. The ultrafast humidity response of GDO is considered to benefit from the unique carbon hybridization of GDO, which contains acetylenic bonds that are more electron-withdrawing than ethylenic bonds in GO, consequently giving rise to a faster binding rate with wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(99 citation statements)
references
References 53 publications
2
97
0
Order By: Relevance
“…In contrast, a greatly increased proportion of oxygenic groups in superhydrophilic GDY was observed (Figure f) and the increased oxygen species was mainly CO group (Figure S3, Supporting Information). In the Raman spectra of superhydrophilic GDY, the acetylenic bond peaks shifted to higher wavenumber with lowered intensity, further confirming some alkyne groups were oxidized to electron‐withdrawing groups (Figure S4, Supporting Information) . All of the observations demonstrated that air‐plasma treated GDY kept the basic skeleton of GDY and the introduced oxygenic groups enabled the superhydrophilicity of GDY from hydrophobicity.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a greatly increased proportion of oxygenic groups in superhydrophilic GDY was observed (Figure f) and the increased oxygen species was mainly CO group (Figure S3, Supporting Information). In the Raman spectra of superhydrophilic GDY, the acetylenic bond peaks shifted to higher wavenumber with lowered intensity, further confirming some alkyne groups were oxidized to electron‐withdrawing groups (Figure S4, Supporting Information) . All of the observations demonstrated that air‐plasma treated GDY kept the basic skeleton of GDY and the introduced oxygenic groups enabled the superhydrophilicity of GDY from hydrophobicity.…”
Section: Resultsmentioning
confidence: 99%
“…c) Water adsorption response of bare (black), GDO‐coated (red), and GO‐coated (blue) Au plates. d) Illustration of the binding model between GO, GDO, and water . Copyright 2018, Wiley‐VCH.…”
Section: Ultrafast and Sensitive Humidity Sensingmentioning
confidence: 99%
“…Very recently,w er eportedf or the first time that graphdiyne oxide (GDO), the oxidized form of GDY, shows an ultrafasth umidity response ( % 12 ms) (Figure 6b), [64] which is three times faster than that of GO ( % 34 ms). By reducing its thickness to approximately 75 nm, the response time wass hortened to 7ms, superior to all other reportedh umidity sensors.…”
Section: Ultrafast and Sensitive Humidity Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It contains diacetylenic linkages (-CCÀ CC-) between carbon hexagons with an extended p-conjugation structure,uniformly distributed pores,low reduction potential, [4] and high carrier mobility. [5] With these distinct physicochemical properties,G DY has been used for many applications such as separation, [6] sensing, [7,8] catalysis, [4,9] and electronic devices, [10] as well as energy storage/conver-…”
mentioning
confidence: 99%